Association of composite dietary antioxidant index and peripheral artery disease: a national cross-sectional study - Fan, Zhi; Zhu, Rongrong; Guo, Shuang; Wu, Qi; Li, Jiazheng; Liu, Shibiao; Su, Zhixiang; Wu, Weiwei (Frontiers in Nutrition, 2025)
The Composite Dietary Antioxidant Index (CDAI), a comprehensive measure of dietary antioxidant intake, quantifies the combined effects of key micronutrients, including vitamins A, C, and E, zinc (Zn), and selenium (Se), to evaluate overall antioxidant capacity. Existing evidence suggests that CDAI is inversely associated with cardiovascular diseases, including myocardial infarction and stroke. This study aims to investigate the relationship between CDAI and peripheral artery disease (PAD), which remains unclear in the current literature. In this study, we analyzed data from 2,332 participants with available ankle-brachial index (ABI) measurements from the NHANES database. Multivariable logistic regression and smooth curve fitting were employed to evaluate the association between CDAI and PAD. Additionally, subgroup analyses and interaction tests were conducted to assess the generalizability and stability of these relationships. Our findings revealed a significant inverse association between CDAI and PAD. In the fully adjusted model, each one-unit increase in CDAI was associated with a 12% reduction in PAD prevalence (OR = 0.88, 95% CI: 0.81–0.95). Moreover, participants in the highest quartile of CDAI had a 53% lower likelihood of developing PAD (OR = 0.47, 95% CI: 0.24–0.93) compared with those in the lowest quartile. These results demonstrate a strong correlation between CDAI and PAD risk, suggesting that diets rich in antioxidants (reflected by higher CDAI scores) may play a role in PAD prevention. However, further comprehensive research and prospective cohort studies are needed to explore causal relationships and validate these findings.